An overview of graphene and its derivatives reinforced metal matrix composites: Preparation, properties and applications. (December 2020) - Zhao, Zhanyong; Bai, Peikang; Du, Wenbo; Liu, Bin; Pan, Duo; Das, Rajib; Liu, Chuntai; Guo, Zhanhu
Abstract: Graphene (Gr) and its derivatives (such as graphene oxide (GO), reduced graphene oxide (RGO), nanoparticles decorated graphene, etc.) reinforced metal matrix composites (MMC) with good structural mechanical properties and functional properties have wide applications in aerospace, automotive, electronics and military fields. However, some problems exist in preparing high performance MMC including poor wettability between Gr-type fillers and metal matrix, and weak interfacial bonding strength. Efficient methods for preparing Gr-related nanomaterials filling metal matrix parts with high performance, especially for complex parts still need be further developed. The engineering application field of Gr MMC needs to be further expanded. In this paper, methods to prepare high performance MMC including surface modification of Gr and its derivatives, properties and applications of these reinforced MMC were reviewed with detailed examples. The main challenges were analyzed and the development trend of Gr-type types reinforced MMC was discussed. Graphical abstract: Image 1 Highlights: Surface modification of graphene improved wettability between graphene and metal matrix. Methods for preparing metal matrix composites were reviewed. Properties of graphene reinforced metal matrix composites were reviewed. Applications of the metal based graphene composites were reviewed.